Blood pressure modulation and cardiovascular protection by melatonin: potential mechanisms behind - Paulis, L; Simko, F (Physiological research, 2007)
The production of the pineal hormone melatonin is synchronized with day-night cycle via multisynaptic pathway including suprachiasmatic nucleus linking several physiological functions to diurnal cycle. The recent data indicate that impaired melatonin production is involved in several cardiovascular pathologies including hypertension and ischemic heart disease. However, the mechanisms of melatonin effect on cardiovascular system are still not completely understood. The activation of melatonin receptors on endothelial and vascular smooth muscle cells and antioxidant properties of melatonin could be responsible for the melatonin effects on vascular tone. However, the data from in vitro studies are controversial making the explanation of the melatonin effect on blood pressure in vivo difficult. In vivo, melatonin also attenuates sympathetic tone by direct activation of melatonin receptors, scavenging free radicals or increasing NO availability in the central nervous system. The central and peripheral antiadrenergic action of chronic melatonin treatment might eliminate the mechanisms counter-regulating decreased blood pressure, providing thus additional cardioprotective mechanism. The extraordinary antioxidant activity and antilipidemic effects of melatonin may enhance the modulation of blood pressure by melatonin and probably play the most important role in the amelioration of target organ damage by chronic melatonin treatment. Further investigation of these mechanisms should provide novel knowledge about pathophysiological mechanisms of cardiovascular diseases, additional explanation for their circadian and seasonal variability and potentially generate new impulses for the development of therapeutic arsenal.
Keywords: Cardiotonic Agents; cévy; antioxidancia; kardiotonika; Blood Vessels; Animals; Humans; krevní tlak; lidé; Blood Pressure; hypertenze; zvířata; Antioxidants; Hypertension; melatonin; Melatonin